2007
DOI: 10.1186/1465-9921-8-70
|View full text |Cite
|
Sign up to set email alerts
|

Truncated recombinant human SP-D attenuates emphysema and type II cell changes in SP-D deficient mice

Abstract: Background: Surfactant protein D (SP-D) deficient mice develop emphysema-like pathology associated with focal accumulations of foamy alveolar macrophages, an excess of surfactant phospholipids in the alveolar space and both hypertrophy and hyperplasia of alveolar type II cells. These findings are associated with a chronic inflammatory state. Treatment of SP-D deficient mice with a truncated recombinant fragment of human SP-D (rfhSP-D) has been shown to decrease the lipidosis and alveolar macrophage accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
69
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 41 publications
7
69
1
Order By: Relevance
“…As c1rfhSP-D used in previous studies includes only a short collagen-like stalk and not the entire collagen-like domain (Fig. 1C), there were controversial observations between and Knudsen et al (2007). This discrepancy led us to hypothesize that the short collagen-like stalk of c1rfhSP-D might suffice to maintain the protein's biological activity.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…As c1rfhSP-D used in previous studies includes only a short collagen-like stalk and not the entire collagen-like domain (Fig. 1C), there were controversial observations between and Knudsen et al (2007). This discrepancy led us to hypothesize that the short collagen-like stalk of c1rfhSP-D might suffice to maintain the protein's biological activity.…”
mentioning
confidence: 89%
“…1A) has been successfully applied in models with acute lung injury (Ikegami et al, , 2007. Regarding the SP-D knock-out mouse model, we have previously demonstrated that a recombinant fragment of human SP-D expressed in E. coli (c1rfhSP-D) exhibited antiinflammatory properties and corrected pulmonary emphysema, hyperplasia of type II cells as well as disturbances of the intracellular surfactant pool Knudsen et al, 2007). Recently, reported that the entire collagen-like domain of this protein is important for correcting some of the pulmonary abnormalities including pulmonary emphysema and disturbed intraalveolar surfactant homeostasis in the SP-D deficient mice by expressing a rat SP-D collagen deletion mutant protein lacking the entire collagen-like domain (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations